(untitled) (Archive of Conferences, 2022)
One of the most important issues in the field of psychology is the research methodology and organization of the study of the motivational-value characteristics of the approach to the treatment of diabetes. Therefore, in the study of the motivational-value characteristics of the individual’s attitude to treatment, it is necessary to make a comprehensive and multifaceted analysis. Health is a priceless treasure not only for man but also for society. This is the first need of a person, which determines his ability to work and ensure his mature development. In Uzbekistan, great attention is paid to the health of citizens, one of the most basic human values.